Track Management Approaches for Underground Tunnel Construction - Damrianant, Jirawat (Thai Journal of Science and Technology, 2023)
The evacuation of muck and transportation of material and equipment within underground tunnels under construction are usually performed using so-called supply trains. Managing the movement of several incoming and outgoing trains on a rail track, designated in this paper as “track management”, is therefore essential to the success of tunnel construction. This research studied two different approaches to track management by using a sizeable drainage-tunnel construction in Bangkok as a case. Petri Net-based models were developed, and COSMOS simulations were performed to gain insight into the two different approaches to track management. The results indicated that the first approach, a rather general one, is easy to manage. However, this approach is prone to an operation-deadlock problem if there is a lack of balance between the number of trains and the number of double-track points along the rail track. The second approach was found to be more complicated to operate but had no deadlock issue. The second approach, therefore, provides flexibility in managing the track, as it allows more combinations of the number of supply trains and the number of double-track points.